Performance Analysis of IOT based Flood Monitoring Framework in Sub-urban - Annisa, Jamali; Jonathan, Peter Giman (2021)
Flooding is the most common natural catastrophe worldwide that occurred without warning which caused great destruction. The government has spent millions of monies on flood mitigation plans. Several systems had been proposed which some of them have been employed around the country. However, it is limited to selected areas due to high installation and maintenance costs. This paper investigates two potential real-time flood monitoring frameworks in the sub-urban area, which are simpler, inexpensive, and require minimum maintenance. The proposed flood monitoring system utilized wireless data transmission system that is either GSM SIM900A module or XBee Pro module. The data was sent to NodeREd for monitoring purposes. From the result, XBee Pro can send more, and faster data as compared to GSM module. The time delay is very much lower for XBee Pro whereby the difference of realtime data captured as compared to the setup time interval that had been set in the system. In terms of consistency and sensitivity, both systems have equal efficacy. In Summary, both systems are adequate to offer monitoring and immediate warning in real-time. However, XBee pro is preferable if the area has internet access. Meanwhile, if the internet service is limited, GSM module can be a good alternative since it does not need Internet access.